1999
DOI: 10.1248/cpb.47.96
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Constituents from Umbelliferae Plants. V. A New Furanocoumarin and Falcarindiol Furanocoumarin Ethers from the Root of Angelica japonica.

Abstract: The CHCl3 extract of the root of Angelica japonica showed high inhibitory activity against human gastric adenocarcinoma (MK-1) cell growth. From this extract, a new furanocoumarin named japoangelone and four furanocoumarin ethers of falcarindiol, named japoangelols A-D, were isolated together with caffeic acid methyl ester, four polyacetylenic compounds (panaxynol, falcarindiol, 8-O-acetylfalcarindiol, and (9Z)-1,9-heptadecadiene-4,6-diyne-3,8,11-triol), eight coumarins (osthol, isoimperatorin, scopoletin, bya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 0 publications
5
75
0
Order By: Relevance
“…The (3S,8S) and (3R,8S)-isomers of 4C were shown to have antimycobacterial activity and to be active against multi-drug resistant strains of S. aureus [298,299]. Acetoxy modifications found in the known Apiaceae acetate 25I and oplopandiol acetate (25H) from Oplopanax horridus increase selectivity towards Mycobacterium spp.. Falcarindiol ethers with furanocoumarins, named japoangelols A-D (25J-M), are novel structures with the potential for enhanced contact toxicity [300]; both polyacetylenes and furanocoumarins in Apiaceae species are known to cause dermatitis. Among these metabolites, falcarindiol had greater in vitro inhibitory activity against human gastric adenocarcinoma cells than any of the ethers 25J-M [301].…”
Section: New Natural Productsmentioning
confidence: 99%
“…The (3S,8S) and (3R,8S)-isomers of 4C were shown to have antimycobacterial activity and to be active against multi-drug resistant strains of S. aureus [298,299]. Acetoxy modifications found in the known Apiaceae acetate 25I and oplopandiol acetate (25H) from Oplopanax horridus increase selectivity towards Mycobacterium spp.. Falcarindiol ethers with furanocoumarins, named japoangelols A-D (25J-M), are novel structures with the potential for enhanced contact toxicity [300]; both polyacetylenes and furanocoumarins in Apiaceae species are known to cause dermatitis. Among these metabolites, falcarindiol had greater in vitro inhibitory activity against human gastric adenocarcinoma cells than any of the ethers 25J-M [301].…”
Section: New Natural Productsmentioning
confidence: 99%
“…The 15 known compounds were identified as (+)-praeruptorin A (2) [20,21], (+)-praeruptorin B (3) [20,21], (+)-praeruptorin E (4) [20][21][22], selinidin (5) [23], cis-3′,4′-diisovalerylkhellactone (6) [19,24], pteryxin (7) [6], suksdorfin (8) [25,26], Pd-Ib (9) [27,28], qianhucoumarin D (10) [20,21], (+)-samidin (11) [25,[29][30][31], laserpitin (12) [32], (9R,10R)-9-acetoxy-8,8-dimethyl-9,10-dihydro-2H,8H-benzo [1,2-b:3,4-b′]dipyran-2-one-10-yl-ester (13) [33], bergapten (14) [34,35], xanthotoxin (15) [36], and falcalindiol (16) [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in well correlation with the previous findings in which the plant extracts were found to induce cytotoxicity on human breast cancer T47D cells (Abdolmohammadi et al, 2008) due to the sensitivity of cancerous cells towards the death flavanoids. Other studies also showed that certain constituents of plant also inhibit the growth of human gastric adenocarcinoma (MK-1), human uterus carcinoma (HeLa), and murine melanoma (B16F10) cells (Fujika et al, 1999). The growth inhibitory effects of other extracts on cancerous cells have also been observed by different investigators on other human cancer cell lines (Li et al, 1995;Kim et al, 2002;Kumi-Diaka and Butler, 2000).…”
Section: Discussionmentioning
confidence: 79%